Mapping the narrow-line Seyfert 1 galaxy 1H 0323+342 - Luigi Foschini; Stefano Ciroi; Marco Berton; Stefano Vercellone; Patrizia Romano; Valentina Braito (MDPI Multidisciplinary Digital Publishing Institute, 2022)
Taking advantage of the most recent measurements by means of high-resolution radio observations and other multiwavelength campaigns, it is possible to elaborate a detailed map of the narrow-line Seyfert 1 Galaxy 1H 0323+342 0323+342 . This map will open the possibility of intriguing hypotheses about the generation of high-energy γ γ rays in the narrow-line region.